ANALYSIS OF THE ADVANTAGES AND CHALLENGES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE IN EDUCATIONAL SYSTEMS - Shingis Urmanov (Bright Mind Publishing, 2025)
The development of technologies in the 21st century radically changes the approach to learning and teaching. One of the most significant trends of recent years is the active implementation of artificial intelligence (AI) in various areas of human activity. AI is already used in medicine (for diagnostics and analysis of medical images), in business (for automation of processes and forecasting), in transport (for example, autonomous cars), in law and even in creative professions.
Keywords: Artificial intelligence, education, personalization, analytics, digitalization, challenges.